2020
DOI: 10.1007/s11442-020-1766-z
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and construction of the glacier mass balance in the Manas River Basin, Tianshan, China from 2000 to 2016

Abstract: The glacier mass balance (GMB) is an important link between climate and water resources and has remarkable regulatory functions in river runoff. To simulate changes of the GMB and to analyze the recharge rates of glacier meltwater to runoff in the Manas River Basin (MRB) during 2000-2016, MOD11C3, TRMM 3B43 and other multi-source remote sensing data were used to drive the degree-day model. The results showed that: (1) the accuracy of the remote sensing meteorological data can be corrected effectively by constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…It can be seen that about 90% of glaciers were mainly distributed in high altitude areas, which was consistent with the results obtained on the spatial distribution pattern of glaciers in China [49]. The potential distribution of the glacier area showed obvious vertical zonality, which might be caused by the significant differences in the environmental factors at different altitudes [50,51]. In terms of the potential distribution of glaciers in various directions (Figure 4), The glacier area in the northeast of Tianshan Mountains in China was the largest, followed by the north, and the west and south were smaller, accounting for about 16% of the total glacier area.…”
Section: Figuresupporting
confidence: 89%
“…It can be seen that about 90% of glaciers were mainly distributed in high altitude areas, which was consistent with the results obtained on the spatial distribution pattern of glaciers in China [49]. The potential distribution of the glacier area showed obvious vertical zonality, which might be caused by the significant differences in the environmental factors at different altitudes [50,51]. In terms of the potential distribution of glaciers in various directions (Figure 4), The glacier area in the northeast of Tianshan Mountains in China was the largest, followed by the north, and the west and south were smaller, accounting for about 16% of the total glacier area.…”
Section: Figuresupporting
confidence: 89%
“…Remote sensing data can solve the problem of spatial continuity, but its resolution limits the precise and objective assessment of the temperature distribution. Therefore, MOD11C3 LST data, which are highly correlated with air temperature, were used as the primary data for the air temperature inversion (Zhao et al, 2020). After considering previous studies and the typical conditions that characterize the geographical location, terrain, and environment of mountainous areas, the longitude, latitude, altitude, slope, pressure, humidity, wind speed, and NDVI were selected to construct a spatial downscaling regression model of air temperature.…”
Section: Construction Of Temperature Downscaling Modelsmentioning
confidence: 99%
“…lyzing glacier changes using remote-sensing data and estimating the changes in volume, as well as assessing their contribution to river runoff [43]. Through the an of Sentinel-1A/1B data and the SRTM DEM in the Manas River basin of the Tia Mountains, it has been observed that the glaciers in this basin are also experiencing loss [44].…”
Section: Study Areamentioning
confidence: 99%
“…Shen et al [42] employed this method to calculate the mass balance of the Tarim River basin glaciers from 1957 to 2000. Another method for calculating GMB is by analyzing glacier changes using remote-sensing data and estimating the changes in glacier volume, as well as assessing their contribution to river runoff [43]. Through the analysis of Sentinel-1A/1B data and the SRTM DEM in the Manas River basin of the Tianshan Mountains, it has been observed that the glaciers in this basin are also experiencing mass loss [44].…”
Section: Introductionmentioning
confidence: 99%